Studi Analisis Risiko Kesehatan dan Keselamatan Kerja Dengan Menggunakan Pendekatan Metode Hirarc Pada Jenis Pekerjaan Bengkel Sektor Industri Informal di Kelurahan Baru Jakarta Timur - Susanto, Agus Joko (LPPM Institut Pendidikan Nusantara Global, 2025)
In 2015, the Ministry of Manpower recorded a provisional total of 21 occupational accident cases in the informal industrial centers, yet no risk analysis had ever been conducted in this sector. This study aims to analyze occupational safety and health (OSH) risks in the informal industry sector in Kelurahan Baru, East Jakarta, using a descriptive-analytic approach with the semi-quantitative HIRARC method. The risk level assessment was carried out by multiplying the values of probability, exposure, and consequences, and then comparing them with the AS/NZS 4360:2004 standard. The study involved 10 respondents, consisting of 2 business owners and 8 workers in the local informal industry sector. The results indicate that the risk level of hazards in a particular type of work can be categorized as either low or high. Based on these findings, it is recommended that business owners and workers implement improvements through OSH programs in the workplace and remain consistently committed to their application.